Chronic recurrent multifocal osteomyelitis on magnetic resonance imaging - Sonia Sandip; S H Chandarashekhara (Indian Journal of Rheumatology)
Chronic recurrent multifocal osteomyelitis (CRMO) is a noninfective auto-inflammatory bone disease; characterized by multifocal involvement of bone. This condition is primarily seen in children and adolescents though sometimes can be found in adults. It is primarily diagnosis of exclusion which is made in conjunction with radiological finding with clinical details with/or histopathology and at present no single test or modality is available to make the diagnosis. Magnetic resonance (MR) imaging can give clue to the diagnosis by demonstration of the involvement of bone in a specific distribution pattern. We report a case of an 11-year-old girl with MR features of CRMO.